Problematika Penerapan Sistem Omnibus Law Ke Dalam Sistem Hukum Nasional Indonesia Melalui Undang-Undang No.11 Tahun 2020 Tentang Cipta Lapangan Kerja - Ahmad Azharil (JOURNAL of LEGAL RESEARCH, 2021)
AbstractThe obstruction of national economic growth due to the long bureaucratic process for business licensing is one of the reasons for the government to create an omnibus law concept in Indonesian Act concerning Job Creation No. 11 of 2020 (JC Act). In fact, the noble ideals outlined in the creation of the JC Act have received a lot of harsh criticism from among the public, workers, academics, and activists in the field of manpower and the environment. Some of the fundamental problems in the creation of the JC Act lie in the absence of public participation in the drafting and deliberation of the Indonesian Parilement, and one of them has the potential to damage environmental sustainability. The omnibus law of the JC Act is a legal model in countries adhering to the common law system that was born due to overcoming regulatory problems in the country caused by the number of regulatory barriers and problems in a field such as the economy. The omnibus law is the concept of simplifying the rules so that they can be implemented properly in order to create an effective, efficient, and stimulating government bureaucracy for national economic progress. Indonesia as a country based on a civil law system is not an obstacle to implementing the omnibus law concept as long as its development and application follows the provisions of the formation of statutory provisions. The concept of the omnibus law contained in the JC Act in the Indonesian national legal system has many substance problems in its articles, including the simplification of the Environmental Impact Assessment (EIA) preparation process by not involving the community as the party whose function is to provide input and correction to the EIA initiator. This will have the potential to sustain the environment as an ecosystem that cannot be separated from people's lives.Keywords : Obstructed, Economy, Creation, Work, Environment